Im having trouble understanding what the (-) after the x applies to. does it make everything in the () negative therefore i will distribute by (6*-x) and (6*-2)?
6-(x+2)≥4-9x

Respuesta :

Answer:

[tex]x \ge 0[/tex]

Step-by-step explanation:

Given

[tex]6-(x+2) \ge 4-9x[/tex]

Required

Solve

[tex]6-(x+2) \ge 4-9x[/tex]

When you distribute -(x+2), the expression becomes:

[tex]6-x-2 \ge 4-9x[/tex]

Collect Like Terms

[tex]9x-x \ge 4-6+2[/tex]

[tex]8x \ge 0[/tex]

Divide both sides by 8

[tex]x \ge \frac{0}{8}[/tex]

[tex]x \ge 0[/tex]

ACCESS MORE